1973
DOI: 10.1111/j.1365-2222.1973.tb01351.x
|View full text |Cite
|
Sign up to set email alerts
|

The airways response to phenylephrine after blockade of alpha and beta receptors in extrinsic bronchial asthma

Abstract: Summary Phenylephrine, a powerful alpha receptor stimulant, has been shown to cause a significant fall in the FEV1 and SGaw in six patients with extrinsic bronchial asthma after prior beta blockade with propranolol. In contrast, propranolol or phenylephrine after prior beta blockade failed to effect a significant change in the FEV1 and SGaw in five normal subjects. The phenylephrine effect can be completely inhibited by alpha receptor blocking drugs, phenoxybenzamine and thymoxamine. These observations suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
2

Year Published

1978
1978
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 19 publications
2
16
2
Order By: Relevance
“…Those agonists contract isolated bronchial smooth muscle [7,8], enhance in vitro secretion of airways submucosal glands [25], and facilitate histamine release from sensitized human lung tissue [26]. These effects probably account for the development of bronchial obstruction ascribed to stimulation of α 1 -adrenoceptors in some asthmatic subjects [7,[27][28][29]. They are also consistent with reported beneficial effects of various α 1 -adrenoceptor antagonists in asthma [30][31][32].…”
Section: Discussionsupporting
confidence: 74%
“…Those agonists contract isolated bronchial smooth muscle [7,8], enhance in vitro secretion of airways submucosal glands [25], and facilitate histamine release from sensitized human lung tissue [26]. These effects probably account for the development of bronchial obstruction ascribed to stimulation of α 1 -adrenoceptors in some asthmatic subjects [7,[27][28][29]. They are also consistent with reported beneficial effects of various α 1 -adrenoceptor antagonists in asthma [30][31][32].…”
Section: Discussionsupporting
confidence: 74%
“…Lately, experiments conducted in vivo prove that clonidine intermediates an inhibitor control of the existing vagal activity. However, these results are not verified by other researchers [12]. Thomson et al [13] has proved that in the group of asthmatics, agonist of alpha-1 adrenergic receptor, inhaled phenilefrine does not affect the airway resistance.…”
Section: Introductioncontrasting
confidence: 52%
“…The existence of «-adrenergic receptors in bronchial asthma was assumed by several investigators, because catecholamines with a-and /(-sympathomimetic properties act as bronchoconstrictors when the /(-adrenergic receptors are blocked [de Kock, 1970;Si monsson et al, 1972;Prime et al, 1972;Patel and Kerr, 1973]. Bacterial endotoxin has been shown capable of potentiating this «-adrenergic activity [Simonsson et al, 1972].…”
Section: Discussionmentioning
confidence: 99%
“…De Kock [1970], Simonsson et al [1972], Prime et al [1972], and Patel and Kerr [1973] have shown that catechol amines like epinephrine or phenylephrine induce an increase of airway resistance in asthmatic patients when the ^-adrenergic system is blocked. This effect can be sup pressed by «-receptor blocking drugs.…”
mentioning
confidence: 99%